DEVELOPMENT OF A DIAGNOSTIC TEST INSTRUMENT TO MEASURE HIGHER ORDER THINKING SKILLS ON RESPIRATORY SYSTEM MATERIAL BASED ON SUSTAINABLE HEALTH ISSUES - Musthofa, Syafri; Kuswanti, Nur; Ichsan, Mochammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The persistently low achievement of Higher Order Thinking Skills (HOTS) among Indonesian students, as reflected in PISA and TIMSS results, is partly attributable to the absence of test instruments specifically designed to diagnose weaknesses in analyzing (C4), evaluating (C5), and creating (C6), rather than merely identifying factual misconceptions. This study aimed to develop a HOTS diagnostic test instrument on the respiratory system topic contextualized within sustainable health issues (PM2.5 air pollution, smoking-related pathophysiology, and communicable respiratory diseases), and to examine its content validity, construct validity, reliability, and the resulting HOTS profile of Grade XI students at Nation Star Academy Surabaya. This Research and Development (R&D) study employed the ADDIE model and produced three parallel instrument sets (Set A, B, and C), each comprising six items (two multiple-choice items for C4, two multiple choice multiple answer items for C5, and two structured essay items for C6) that synthesized the Merdeka Curriculum Fase F Learning Outcomes with the Cambridge AS & A Level Biology Learning Outcomes. A limited field trial was conducted with 50 Grade XI Science students. Results showed very strong content validity (mean Aiken's V = 0.907). Construct validity, examined through corrected item-total correlations, sub-scale internal consistency, and exploratory factor analysis, provided initial but not fully confirmed evidence: the creating dimension (C6) proved the most empirically stable (item-total r up to 0.781), while analyzing (C4) and evaluating (C5) showed sensitivity to item format and stimulus heterogeneity (case specificity). Internal consistency reliability was acceptable for formative diagnostic purposes (Cronbach's Alpha = 0.623; McDonald's Omega = 0.642). The HOTS profile showed a declining gradient across cognitive levels: analyzing (C4) was high (72.00%), evaluating (C5) was moderate (46.67%), and creating (C6) was low (39.83%), indicating a gap in knowledge transfer toward argumentative evaluation and evidence-based creative problem formulation. The instrument is recommended as a formative diagnostic tool for teachers designing differentiated instruction, with the caveat that additional items per cognitive dimension and stimulus homogeneity are needed in further development to strengthen construct validity evidence. Keywords: ADDIE; diagnostic test instrument; HOTS; respiratory system; sustainable health issues